What are the current practices employed by audiologists in early hearing detection and intervention in the South African healthcare context?. (February 2021) - Khoza-Shangase, Katijah; Kanji, Amisha; Ismail, Fatima
Abstract: Background: Universal access to early hearing detection and intervention (EHDI) forms part of the audiology community's goal. Evidence on current practices employed by South African audiologists in EHDI in order to ensure this universal access and success for children with hearing impairment is therefore required, hence this study. Methods: A quantitative survey research methodology with a cross-sectional design was employed. An online survey was completed by 49 qualified audiologists and dually qualified speech therapists and audiologists. Data were analysed using descriptive statistics. Results: Results identified gaps in the implementation of EHDI within the South African context. A total of 83.7% of the participants were involved in newborn hearing screening (NHS), with over half adopting the targeted screening approach instead of universal NHS services (UNHS). Capacity versus Demand challenges play a significant role in the lack of successful implementation of NHS with over 60% of the audiologists in the sample reporting that NHS is and should only be conducted by audiologists only; with minimal evidence of task shifting found. No standardised screening protocol was found, with challenges around budget allocation for EHDI revealed. Conclusions: Although progress has been noted, a) gaps between public and private healthcare sector resources allocations and availability, b) limited contextually responsive strategic planning, as well as c) lack of translation of knowledge, policies and guidelines into practice, are glaring areas that require attention by the South African audiology community.